2020
DOI: 10.1038/s41598-020-63803-0
|View full text |Cite
|
Sign up to set email alerts
|

Gamma glutamyltransferase and risk of dementia in prediabetes and diabetes

Abstract: Diabetes is associated with cognitive impairment and greater risk for dementia, but the role of gammaglutamyltransferase (γ-GT) in dementia has not been elucidated. We determined incident dementia including Alzheimer's disease and vascular dementia, analyzing data from participants aged 40 years or older in the National Health Insurance Database, collected by the National Health Insurance Service in Korea, from January 2009 to December 2015. During a median follow-up of 7.6 years, 272,657 participants were dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…One population-based study found that NAFLD was independently associated with a 16% increased risk of overall dementia (HR 1.22 for vascular dementia, HR 1.07 for AD) [ 124 ]. Another population-based study found that physically frail NAFLD patients with high risk of liver fibrosis were at a 5-fold increased risk of receiving a dementia diagnosis over a 8-year period, while physical frailty nor high risk of liver fibrosis were independent risk factors on their own [ 125 ].…”
Section: Possible Mechanisms Behind Cognitive Dysfunction In Nafldmentioning
confidence: 99%
“…One population-based study found that NAFLD was independently associated with a 16% increased risk of overall dementia (HR 1.22 for vascular dementia, HR 1.07 for AD) [ 124 ]. Another population-based study found that physically frail NAFLD patients with high risk of liver fibrosis were at a 5-fold increased risk of receiving a dementia diagnosis over a 8-year period, while physical frailty nor high risk of liver fibrosis were independent risk factors on their own [ 125 ].…”
Section: Possible Mechanisms Behind Cognitive Dysfunction In Nafldmentioning
confidence: 99%
“…GGT is routinely utilized in clinical practice to assist clinicians in identifying the presence of liver injury. However, increased serum GGT is reported to be associated with metabolic syndrome (7), chronic kidney disease (8,9), dementia (10,11), and even malignant tumors (12). Recently, GGT has been demonstrated as the hallmark of oxidative stress; this enzyme can induce pro-oxidant reactions, which play an essential role in tumor formation and cell proliferation (13).…”
Section: Introductionmentioning
confidence: 99%
“…The date of dementia diagnosis was defined as the date when the prescription of an anti-dementia medication and registration of a dementia code coincided. The diagnostic criteria for dementia based on ICD-10 codes have been reported in previous studies (17,18). Among the entire national population, 8,080,619 patients diagnosed with insomnia between 2007 and 2014 were included in this study.…”
Section: Participantsmentioning
confidence: 99%